Implementasi Market Day dalam Penguatan Karakter, Jiwa Kewirausahaan, dan Profil Lulusan Murid Kelas VI di MIS Muhammadiyah 3 Al-Furqan - Fahrina Inayah; Hikmah Hikmah; Azkya Nurmadina; Lara Nuzila; Laily Mahfuzhah; Aslamiah Aslamiah; Diani Pratiwi; Lara Syifa (Science and Education Journal (SICEDU), 2026)
This study aims to describe the implementation of Market Day at MIS Muhammadiyah 3 Al-Furqan as an effort to strengthen students’ character, foster entrepreneurial spirit, and support the formation of students’ graduate profiles. This research employed a descriptive qualitative approach, with data collected through interviews, documentation, and literature study. The research informants consisted of the head of the madrasah, the vice principal for curriculum affairs, and an alumnus. Data validity was ensured through source triangulation and technique triangulation. Meanwhile, data analysis used the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that Market Day is a regular school program conducted after the final school examination and participated in by sixth-grade students. This activity teaches students through product planning, material preparation, selling activities, customer service, and simple business result management. Through this program, students learn values such as independence, responsibility, discipline, honesty, self-confidence, cooperation, and entrepreneurship. Therefore, Market Day supports contextual learning, the Merdeka Curriculum, the Love-Based Curriculum, and the development of students’ profiles.